UTILIZATION OF JELEKONG ART VILLAGE AS RESEARCH SOURCE OF SOCIAL STUDIES: Descriptive Study in Jelekong Art Village - niswanti, rahmi (International Journal Pedagogy of Social Studies, 2019)
The problem in this study is that there are many educators who are only slaves to the curriculum, where in doing their learning in class, educators do not provide meaningful learning that only focuses on textbooks and without utilizing the surrounding environment as a source of learning. Though the task of the teacher in learning is not limited to the delivery of information to students only, but according to the progress and demands of the times, teachers must understand various effective learning models in order to guide students optimally. Mulyasa (2009, p.21).According to Komalasari (2011, p. 12), the learning process and learning of social studies should be influenced by environmental factors that become environmental inputs and instrumental input is a factor that is intentionally designed to support the teaching and learning process and the output that you want produced. One source of social studies learning that utilizes the surrounding environment is by visiting places that are interesting and can be linked to social studies learning material. This study aims to determine the utilization ofÂ  Kampung Seni Jelekong as a social science learning resource. The approach used is the approach to research and development (research and development) refers to the 4D model with the stages of define, design, develop and disseminate , but in this study only until the third stage is develop. Data collection techniques by means of documentation studies, interviews and questionnaires. The data analysis process in this study is done by sorting and organizing data . The results of the study show that Jelekong Art Village is suitable for use in social studies learning activities through learning tools in the form of social studies learning modules.